Hemangiopericitoma. - I Nobre; O Fernandes; V Garcia; J Manaças; J B Reis; J M Pisco (Acta Médica Portuguesa, 1995)
A case of hemangiopericytoma located in the left upper thigh is presented. The literature is reviewed, particularly the clinical aspects and reference is made to arteriography and preoperative embolization.